Evaluation of adjunctive analgesia with intrathecal fentanyl along with hyperbaric bupivacaine in spinal anesthesia for elective cesarean section - Surana, Ranu Neelamchand; Jain, Trishala (International Journal of Research in Medical Sciences, 2020)
Background: Cesarean section (CS) is one of the most common surgical procedures in female patients. Authors aimed to evaluate the postoperative analgesic efficacy of adding intrathecal fentanyl to bupivacaine, and its effect on the onset and duration of spinal anesthesia along with its effect on mother and neonate. Methods: Study was performed on 60 cesarean section parturients divided into two groups. Group F received 2 ml of 0.5% hyperbaric bupivacaine (10 mg) plus 0.4 ml fentanyl (20 µg), and Group B received 2 ml of 0.5% hyperbaric bupivacaine (10 mg) plus 0.4 ml of normal saline. The parameters taken into consideration were pain scores, analgesic requirement, hemodynamic stability and side effects. Results: It was found that duration of sensory block was prolonged in fentanyl group (111 minutes vs 86 minutes, p<0.001). Duration of effective analgesia (174.36 minutes vs 127.81; p value <0.001) were also found to be prolonged in Group F with requirement of fewer postoperative analgesics (1.02 vs 2.76, p=0.03). There was not much difference in the occurrence of side effects in both the groups. Conclusions: Addition of fentanyl to intrathecal bupivacaine for cesarean section increases the duration of postoperative analgesia without increasing maternal or neonatal side effects.